A PRAÇA DE PROTÓTIPOS NO PARQUE DE INOVAÇÃO E SUSTENTABILIDADE DO AMBIENTE CONSTRUÍDO - Blumenschein, Raquel Naves; Umakoshi, Erica; Ferrari, Maria Vitoria; Barros, Orivaldo (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The current scenario of the built environment production process has been influenced by climate, geopolitical and natural changes, requiring that changes must be accelerated towards increasing productivity and performance, in order to ensure that the construction sector fulfill its role of building with innovation and cost reduction, contributing to the resilience of the built environment. In this sense, it is necessary to promote the approximation of the sector that produces the scientific knowledge to the sector that uses this knowledge. This approach can be accomplished through Research Parks. Thus, this article aims to present the partial results of a research project that aims to exercise models of integration and collaboration between the academy, the productive sector of CPIC and the public sector, through the construction of Pisac - Park of Innovation and Sustainability of the Built Environment, more specifically with a focus on the Prototypes Square.